Implementasi Hormon Ga3 (Giberelin Acid) Dan Abc Mix Pada Tanaman Padi Hitam Secara Soilless Culture - Ningtias, Epi Nindia Pustika; Muhklisin, Ilham; Widodo, Tirto Wahyu; Alif, Trisnani (Agropross : National Conference Proceedings of Agriculture, 2025)
Soilless rice cultivation has weaknesses, one of which is that the fertilizer applied is not clearly formulated and has side effects in the form of a slower flowering time compared to conventional rice cultivation. The aim of this research was to analyze the addition of gibberellin hormone (GA3) and ABC-Mix fertilization in Soilless black rice cultivation. This research was designed using a completely randomized split plot design with two factors and three replications. The first factor is the GA3 concentration which consists of control and 200 ppm, while the second factor is the ABC-Mix concentration which consists of 700-800 ppm; 1000-1050 ppm; 1250-1300 ppm, and 1500-1550 ppm. Observation variables consisted of plant height, panicle length, root length, flower emergence time, total number of tillers, number of productive tillers, number of clump grains, number of perennial grains, and weight of 1,000 grains. Analyzed using Duncan Multiple Range Test and Tukey. The results showed that there was an interaction between GA3 concentration and ABC Mix concentration on the number of productive tillers (25.00 tillers), the weight of the grain (3.92 grams), the weight of the grain per hill (47.57 grams), and the weight of 1000 grains (26.66 grams). The GA3 concentration of 200 ppm had the best effect on the variables of plant height (88.97 cm), total number of tillers (30.00 tillers), flower emergence time (72.58 days), and panicle length (48.24 cm). Meanwhile, the ABC Mix concentration of 1250-1300 ppm had the best effect on the empty grain weight variable per panicle (0.58 grams)